PENILAIAN EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER PADA SKPD PEMKAB TABANAN - Wower, Sri Dewi Danu Utami (E-Jurnal Akuntansi; Vol 1 No 1 (2012), 2012)
ABSTRACT Information technology is a system that helps people to fulfill their daily needs which will continue to increase. As information technology advances, government as an institution switching on the utilization of computer-based information systems particularly in the field of accounting with the hope to improve the performance and is useful in helping the operational. Regional Financial Management Information System (RFMIS) is an accounting information system that is used on the Work Unit of Regional Device (WURD) Tabanan regency. RFMIS is a new program that replaces Regional Management Information System (RMIS), but RFMIS not been able to integrate the data quickly. This study conducted on WURD in Tabanan regency government which aims to determine the effectiveness of the implementation RFMIS. Data collection methods used are observation, interviews and questionnaires. Test instruments used are validity and reliability testing. The analysis technique used is quantitative analytical technique using Likert scale. Based on the analysis it is known that the effectiveness of RFMIS on WURD in Tabanan regency government assessed from all variables included in the effective criteria. Viewed from each variable, the majority of respondents expressed an effective on variable of data security, effective on variable time, effective on variable precision, effective on variable relevance, effective on variable variation reports, effective on variable of physical comfort, effective on quality of information variable and effective on information technology variable. Keywords : Effectiveness, Regional Financial Management Information System
Keywords: Effectiveness, Regional Financial Management Information System